MO-500 Microsoft Access expert certification. (Packt Publishing, 2022)
Prepare for the MO-500 Microsoft Access Expert Certification Exam About This Video Learn all the techniques specified for the Microsoft Access Expert MO-500 Certification Exam Learn how best to prepare to take the MO-500 exam Be familiar with the standard and format of the MO-500 exam with our sample certification exam In Detail This course will prepare you to successfully pass the MO-500 Microsoft Access Expert certification exam. The MO-500 is the only exam officially recognized by Microsoft for Access 365 Apps and Access 2019. Every aspect of the exam is covered in detail, together with exercises and solutions. If you take this course and follow the guidelines provided, you will enhance your chances of obtaining this extremely valuable qualification. Prove your database skills by obtaining independent certification from Microsoft. The course is designed to ensure that you are familiar with all the techniques specified by Microsoft for the MO-500 Objective Domain (Syllabus). Every aspect of the requirements specified by Microsoft is comprehensively covered using video lectures together with appropriate exercises designed to ensure your understanding of the database techniques covered in each of the lectures. The exercises have been designed so that when you take the actual exam, you will be fully prepared for the standard and style of the projects and tasks set by Microsoft. By the end of this course, you will be well prepared for your MS-500 exam. Audience This course is suitable for beginners and designed for all students who wish to obtain the Microsoft Access MO-500 Expert Certification. No prior knowledge is assumed; just Microsoft Access 2016 or Microsoft Access 365/2019 is required for practice.